Technological Assessment of Starch Edible Coating and Its Application on Primary Packaging of Durian Sweets - Budi Santoso; Daniel Saputra; Rindit Pambayun (Jurnal Teknologi dan Industri Pangan, 2004)
The study objective was to determine the shelf life of edible coating packaged of durian lempok. The experimental method used in this study was Factorial Randomized Block Design consisting of three factors. These factors were tapioca starch, stearate acid, and CMC. The edible coating solution was applied in to durian lempok by using dip method. The result showed that edible coating packaged of durian lempok could increase the durian lempok shelf life by 67 percent than durian lempok without edible coating. The edible coating was capable of decreasing the durian lempok weight loss by magnitude of 36.38% during storage, decreasing the peroxide number by magnitude of 33.33%, decreasing the water content by magnitude of 7.54%, and suppressing the microbial growth by the amount of 31.20%, respectively. Visual change of non-coating lempok had occurred on the day of 19th, which was indicated by greyish-white colour change due to certain type of mold on lempok surface, while the similar change happened at day of 31th (T2A3C3 treatment). Key words : Tapioca, CMC, stearate acid and edible coating.